American Cold War Strategy and the Absence of "Swift and Effective Retribution" for the 1983 Marine Barracks Bombing. Issue 2 (3rd April 2022) - Cummins, Nicholas
ABSTRACT: Ronald Reagan entered the White House in 1981 as the president who promised to confront the foreign enemies of the United States. Whilst the Soviet Union remained the single greatest threat to the United States, the 1979 hostage crisis in Iran dramatically raised concerns over international terrorism. Reagan's approach to this threat was unequivocal – those responsible would be subject to "swift and effective retribution". In 1983, one of the most devastating acts of international terrorism in American history confronted Reagan – the bombing of the Marine barracks in Lebanon. Despite Reagan's earlier pledge, those believed to have been responsible for this attack – Iran and its surrogate, Hezbollah – avoided punishment. This analysis explains the discrepancy between Reagan's rhetoric and his actions by examining how strategic imperatives related to the Cold War helped deter a military reprisal against both Iran and Hezbollah.